Jurnal Kata: male and female atitudes towards swear worlds: a case study at binus International school - Maria fe s. nicolau, Katharina endriati sukamto (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
swear worlds are generally used to articulate anger, pain, excitement, frustration, or surprise